Role of International Criminal Court in Reducing Human Rights Violations - Othman, Adel Hamzah (International Journal of Criminology and Sociology, 2022)
Crimes against human rights and military conflicts within and between states are forcing the international community to take collective responsibility for peace and prevention of such incidents. An important factor in this direction is the accountability of those who commit crimes against humanity. Apart from representatives of the judicial system of each individual country, this role is assigned to the International Criminal Court (ICC). While its role in the investigation of military conflicts and crimes against human rights has been questioned by a series of setbacks, it is impossible to deny the ICC’s impact on peace. To identify the role of the ICC in the establishment and protection of human rights, authors analyse closed and open criminal investigations throughout the history of the Court. Analysis of the criminal cases opened in 4 countries is provided, namely: Uganda, Kenya, Sudan, and Iraq. The obtained data demonstrate that investigations are more effective in countries that are members of the Rome Statute. With more power, the International Criminal Court can work more effectively with the governments of these states and hold those responsible for crimes against humanity to account. Thus, in Sudan, the pre-trial investigation in several cases has been going on for more than 10 years, the trial itself has not yet begun. In the Iraq-UK case, the ICC Attorney’s Office also failed to obtain justice for the perpetrators of crimes against Iraqi citizens. The authors recommend addressing this factor and consider an in-depth study of the ICC statute. Changes in international criminal justice require flexibility from relevant organisations and their statutes.